2011
DOI: 10.1111/j.1750-3841.2010.02004.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Gamma Radiation Dose Rate on Psychrotrophic Bacteria, Thiobarbituric Acid Reactive Substances, and Sensory Characteristics of Mechanically Deboned Chicken Meat

Abstract: Frozen samples of mechanically deboned chicken meat (MDCM) with skin were irradiated with gamma radiation doses of 0.0 kGy (control) and 3 kGy at 2 different radiation dose rates: 0.32 kGy/h (3 kGy) and 4.04 kGy/h (3 kGy). Batches of irradiated and control samples were evaluated during 11 d of refrigerated (2 ± 1 °C) storage for the following parameters: total psychrotrophic bacteria count, thiobarbituric acid reactive substances (TBARS), evaluation of objective color (L*, a*, and b*) and a sensory evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In their research, TBARS values increased as concentration of ascorbic acid in the meat increased due to the ascorbic acid could act as a prooxidant at low concentrations. Control (no added antioxidant); BHA: 200 mg.kg -1 butylated hydroxyanisole; CAR: 300 mg.kg -1 L-carnosin; PA: 300 mg.kg -1 phytic acid Brito et al (2011) the TBARS values for the irradiated samples increased significantly (P < 0.05) in comparison with the control samples after the 7th day of refrigerated storage.…”
Section: Resultsmentioning
confidence: 98%
“…In their research, TBARS values increased as concentration of ascorbic acid in the meat increased due to the ascorbic acid could act as a prooxidant at low concentrations. Control (no added antioxidant); BHA: 200 mg.kg -1 butylated hydroxyanisole; CAR: 300 mg.kg -1 L-carnosin; PA: 300 mg.kg -1 phytic acid Brito et al (2011) the TBARS values for the irradiated samples increased significantly (P < 0.05) in comparison with the control samples after the 7th day of refrigerated storage.…”
Section: Resultsmentioning
confidence: 98%
“…In present study, chicken meat with skin were utilized. High lipid concentrations in raw materials make them more vulnerable to oxidation and discoloration [10]. Ahn et al [11] demonstrated that animal species, irradiation dose and muscle type influence the color variations in irradiated meat.…”
Section: Resultsmentioning
confidence: 99%
“…Khalid et al [12] reported that variable b* (yellowness) was the main factor for the color variability, since chicken meat was basically yellow. Iron, as myoglobin molecules, are sensitive to chemical alterations as well as modifications in energy input, which altered the structure of the irradiated meat during refrigeration [10,13]. Due to differences in pigmentation, the value of a* is greater in native than broiler meat.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the exchange current densities for the partial reactions are very much higher than for the same reactions on stainless steels, for example, and these affect the value of the measured potential. An example of the calculated E redox vs Using the methods outlined above, we show in Figure 8 the calculated evolution of the composition of irradiated water at 25 °C for a γ-photon dose rate of 100 mGy/s, which is somewhat higher than the dose rate employed by Britto et al [90] (1 mGy/s) in their experimental work on the effect of radiation dose rate on psychrotrophic bacteria, thiobarbituric acid reactive substances, and sensory characteristics of mechanically deboned chicken meat. The calculations are for a closed, liquid phase system (no gas phase) and it is seen that the system comes to a steady state after an irradition time of 105 s (27.8 hrs), with this time depending strongly upon the dose rate and hence on the rates of the various reactions in the radiolysis mechanism (Table 4), because the rates of those reactions depend upon those same concentrations.…”
Section: Nomentioning
confidence: 89%
“…by Catanescu and Tofana [88] while the international standards are articulated in Ref 89. The dose rates employed in γ-photon ( 60 Co) irradiation range up to 0.5 Gy/s, depending upon the food and the microorganisms present, although many dose rates are apparently much lower (e.g., 1.12x10 -3 Gy/s [90]). In any event, at a dose rate of 0.1 Gy/s it takes 500,000 s (139 hrs) to accumulate a 50 kGy dose, which is the upper end of the range employed in the food industry.…”
Section: Nomentioning
confidence: 99%